Daya CMT Sdn Bhd / Noralajani Mohammad Aldwi - Mohammad Aldwi, Noralajani (2017)
All students in Diploma of Civil Engineering are compulsory to undergo the Industrial Training at least EIGHT (8) weeks during the semester break at the end of the third year student for the semester 4 and above. In Industrial Training, the students will be monitored with their industrial supervisor in the company. The Daya CMT Sdn Bhd is my Industrial Training was done that situated in Bayan Lepas, Penang. I was placed in the B589 of B Braun Medical Industries Sdn Bhd, Penang as my site office. I choose Daya CMT Sdn Bhd for my Industrial Training because it near from my house and the transportations are easily to get. In this report for the chapter one are consists the background of the company, organization chart, vision and mission of the company. Next, for the chapter two is about weekly summary based on the logbook that I wrote every day and was signed by my supervisor. Besides that, for the chapter three, it all about the technical report that I had gained along Industrial Training and the problem encountered and how to overcome it. Finally, for the last chapter is about the conclusion I had got through my Industrial Training. The project on the B Braun Medical Industries Sdn Bhd are to proposed extension to existing manufacturing facility at Campus 1 comprising of: • New 6 story production and car parks B9 building • New 4 story office and plant room B9 Spine building • New 2 story cafeteria B5 Building • New 8 story with sub-basement B8 office building